2006
DOI: 10.1246/cl.2006.1002
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Base-catalyzed Alkynylation of Carbonyl Compounds with Trimethylsilylacetylenes

Abstract: Alkynylation of carbonyl compounds with trimethylsilylacetylenes in the presence of a catalytic amount of Lewis bases such as acetate or phenoxide anion is described. The alkynylation proceeded under mild conditions and afforded the corresponding propargyl alcohols in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…in N , N ‐dimethylacetamide (DMA), which furnished desired product 3a in 12 % yield (Table , entry 1). The reaction was then conducted with 2 equivalents of NaOPh, as phenoxides are known to activate organosilanes,, Fortunately, 3a was isolated in 76 % yield (Table , entry 2) under these conditions. Next, various solvents were screened to increase the product yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in N , N ‐dimethylacetamide (DMA), which furnished desired product 3a in 12 % yield (Table , entry 1). The reaction was then conducted with 2 equivalents of NaOPh, as phenoxides are known to activate organosilanes,, Fortunately, 3a was isolated in 76 % yield (Table , entry 2) under these conditions. Next, various solvents were screened to increase the product yield.…”
Section: Resultsmentioning
confidence: 99%
“…Organosilanes such as alkynyl, acetate, allyl, propargyl, benzyl, dithiane, aryl, and enolates can react with carbonyls and imines. These reactions proceed in the presence of either catalytic or stoichiometric amounts of Lewis bases such as tetrabutylammonium fluoride (TBAF), KOEt, tetraalkylammonium phenoxide, NaOPh/1,2‐(O=PPh 2 ) 2 C 6 H 4 , and Me 3 SiOK/Bu 4 NCl , . However, despite their potential applications, the hydroxymethylation of organosilanes by using formaldehyde as an electrophile has not been examined in detail , .…”
Section: Introductionmentioning
confidence: 99%
“…We designed 1-pentafluorophenyl-4-[(trimethylsilyl)ethynyl]benzene 1 as a monomer and examined its polymerization with a catalytic amount of fluoride anions ( Scheme 1 ). This is because fluoride anions were found to catalyze silylacetylene activation for subsequent reaction with a number of electrophiles, 6 , 7 and also because regioselective S N Ar reactions of perfluoroaryl groups with nucleophiles 8 , 9 are well studied. Very recently, we demonstrated the transition-metal-free polymerization of 2-perfluoroaryl-5-trimethylsilylthiophenes promoted by fluoride anions to afford polymers with controlled MWs and low PDIs.…”
Section: Resultsmentioning
confidence: 99%
“…In 2006, Mukaiyama and co‐workers established an aldehyde alkynylation protocol by using a 1‐phenyl‐2‐trimethylsilylacetylene and a catalytic amount of phenoxide anions (Scheme ) 1. In this report, Mukaiyama showed that phenoxide is an excellent desilylation agent for terminal alkynes.…”
Section: Methodsmentioning
confidence: 99%